Pemanfaatan Kain Flanel sebagai Alat Peraga Pendidikan Bagi Anak Usia Dini - Siti Qomariyah; Ummi Rosyidah; Irma Ayuwanti; Santi Widyawati (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
This service aims to provide training in utilizing flannel as a prop for early childhood. The method used in this service is First, Strengthening knowledge about the importance of learning media and their use in learning activities. Provide insight into learning media appropriate for early childhood.  Second, the introduction of learning media that can be applied in the classroom, and finally training on making educational props made of flannel along with the determination of learning steps in the classroom carried out by the entire service team and service participants.  The result of this service is that participants succeeded in making a busy book with the theme of knowing numbers, recognizing letters, and counting which is included in the excellent category.   Keywords: Bussy book, flannel, props